Serviço para Product Placement em Televisão - André Casais Regado (2017)
The increase of video consumption under digital format is evident. Nowadays everyone has a smartphone or tablet, where they can watch television. Usually, these devices have Internet access which allows us to contextualize ads according the end user. The way to display ads in video are changing. Conventional advertising Ad Breaks are dying because they became inefficient. Native Advertising is the new way to display advertising, where the ads will be embedded in the video content so that the viewer can't reject the advertisements' messages. \parNowadays, no one offer different objects placed in video (NIVA) based on user's network location which allows us develop a new and innovate project.To achieve this, we will have a repertoire of small segments of the programme with different products placed in them, this is because producing NIVA advertising is computationally intensive. Personalized adverts based on location can be efficient because they will permit to reach possible clients at the precise moment. This thesis presents a high-level architecture for product placement in television, where the goal is to create a platform that allows an insertion of personalized segments, in real time, using Adaptive Bitrate Streaming, namely, MPEG-DASH. The viewer will see the program in real time, but the architecture will be switching streams seamlessly between main program scenes, selected stream of program with most appropriate item placed in it and back to the main program stream. From a WEB interface it will be possible view the final video.